God can permit apparently gratuitous suffering and abandonment - Koh, Daniel (Nanyang Technological University, 2024)
In this paper, I consider a contemporary argument against Christian theism from a focus on skeptical theism and the parent-child analogy and argue that it fails in three ways. The argument against Christian theism is this, that a Christian God who has a relationship with humans akin to the relationship between a parent and child, would not permit His children to experience the conjunction of apparently gratuitous suffering and abandonment. I argue that it fails in three ways: first in its failure to acknowledge other beliefs associated with Christian theism, second in its commitment to a clause underminable by skeptical theism, and third in its narrow focus on the parent-child analogy itself. These failures instead support the claim that a Christian God can permit apparently gratuitous suffering and abandonment. I begin with an exposition of the literature leading up to skeptical theism and the parent-child analogy. Then, I explicate on Wielenberg’s argument from apparently gratuitous suffering and abandonment. Thereafter I expound on my three objections against Wielenberg’s argument. Finally, I consider some implications on Rutledge’s paper that uses the same parent-child analogy to argue against skeptical theism before concluding.